Effects of Alprostadil Combined with Edaravone on Inflammation, Oxidative Stress and Pulmonary Function in Patients with Traumatic Hemorrhagic Shock: Alprostadil with Edaravone on traumatic Hemorrhagic Shock - Luo, Dong; Pan, Qingmei; Wang, Linlin; Zhao, Wenfeng; Bao, Wentao (Cellular and Molecular Biology, 2022)
The study aimed to explore the roles of alprostadil combined with edaravone in inflammation, oxidative stress and Pulmonary function in patients with traumatic hemorrhagic shock (HS). 80 patients with traumatic HS treated in Feicheng Hospital Affiliated to Shandong First Medical University and Tai’an City Central Hospital from January 2018 to January 2022 were enrolled and divided into observation group (n=40) and control group (n=40) according to the randomized control method. Patients in the control group were given alprostadil alone (5 g alprostadil + 10 mL normal saline) in addition to conventional treatment, while those in the observation group received edaravone (30 mg edaravone + 250 mL normal saline) on the basis of treatment in the control group. The patients in both groups were treated via intravenous infusion once a day for 5 days. 24 hours (h) after resuscitation, venous blood were collected to detect serum biochemical indicators such as blood urea nitrogen (BUN), aspartate aminotransferase (AST) and alanine aminotransferase (ALT). Enzyme-linked immunosorbent assay (ELISA) was conducted to determine serum inflammatory factors. Lung lavage fluid was collected to examine pulmonaryfunction indicators such as myeloperoxidase (MPO) and matrix metalloproteinase-9 (MMP-9) activity and to observe the oxygenation index (OI). Blood pressure was measured at admission and 24 h after surgery. The observation group had significantly lowered serum BUN, AST and ALT (p<0.05), the content of serum interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) as well as oxidative stress indexes like superoxide dismutase (SOD) and malondialdehyde (MDA) (p<0.05) and pulmonary function indicators (p<0.05) but overtly increased content of SOD and OI. Furthermore, the blood pressure in the observation group dropped to 30 mmHg at admission and rose to the normal range. Alprostadil combined with edaravone effectively reduces inflammatory factors and improves oxidative stress and pulmonary function in patients with traumatic HS, whose efficacy is significantly better than that of alprostadil alone.